A New species of the bee, Anthophora Latreille, 1803(Hymenoptera: Apidae) from Kurdistan region-Iraq - Amin, Havall M; Mawlood, Nabeel A. (Kurdistan Journal of Applied Research, 2017)
A New species of the family Apidae, Anthophora sulaimanensis sp. nov. Is described; main parts illustrated and got comparisons with its nearly- related species from Iraq-Kurdistan region. The species is characterized by Mandibles black, bi dentate; Labrum black with two brown sculptures on lateral basal sides; Clypeus without sculpture; Marginal cell of the fore wings broadly rounded apically, strongly bent away from wing margin. The important taxonomic parts have been drawn. Localities, plant visiting and collections date have been mentioned.